INDONESIA'S GREEN, RED ECONOMIC SECTORS AND BANKING CREDIT RATES - Heru Setyo Handogo; Irene Rini Demi Pangestuti (Lafadz Jaya Publisher, 2023)
This research is to analyze the influence of economic sectors on loan interest rates given, by linking it to the issue of sustainable finance. This research tries to see whether there are differences in credit interest rates given by banks in Indonesia to economic sectors that support the environment (green) and economic sectors that support the environment. endangers the environment (red). The research uses samples from bank data in Indonesia for the period 2016 to 2021. Credit data is mapped to green and red economic sectors with criteria according to the Indonesian Green Taxonomy. Data is processed by panel regression using the fixed effect model. The results of the study show that there is a negative and significant relationship between green credit and loan interest rates. On red credit, although it has a positive correlation, it is not statistically significant.